Application of the Business Model Canvas in Determining Business Development Strategies at Kedai Kabur Bontang - Wardana, Muhammad Harsa; Tosungku, La Ode Ahmad Safar; Sitania, Farida Djumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
Kedai Kabur is a shop that sells various kinds of porridge, such as chicken porridge, black sticky rice porridge as well as coffee and non-coffee drinks. Kedai Kabur has a problem, namely the lack of interest from customers who come to the shop. This research aims to find out the description of the Kedai Kabur business model when viewed from the Business Model Canvas aspects and to find out the Kedai Kabur Business Model Canvas strategy to be recommended based on the Business Model Canvas Transformation Design. In formulating strategies, researchers use a business model canvas which consists of nine blocks, namely, customer relationships, key partners, value proposition, customer segments, channels, revenue streams, key resources, key activities and cost structure. This research uses qualitative methods with analysis using the business model canvas and also using SWOT. Data collection techniques use observation, interviews and questionnaires. The results of this study show that Kedai Kabur has basically implemented the Business Model Canvas and strategies recommended with the Business Model Canvas model, namely by targeting customers who like porridge and customers among teenagers, serving customers kindly and taking a personal approach to consumers, making sales through Grabfood, and promoting more often.